ANALYSIS OF STUDENTS' CREATIVE THINKING ABILITY AND LEARNING INDEPENDENCE IN SOLVING STORY PROBLEMS ON THE SUBJECT OF LINEAR EQUATIONS WITH TWO VARIABLES (SPLDV) - Zagoto, Desri Lenta Sari (Universitas Nias Raya, 2024)
The research was motivated by the lack of students' creative thinking abilities and independent learning in solving story problems on SPLDV material. The aim of this research is to describe: (1) Students' thinking abilities in solving story problems in class VIII SPLDV material at SMP Negeri 4 Maniamolo, (2) Students' learning independence in solving story problems in class VIII SPLDV material at SMP Negeri 4 Maniamolo. This type of research is qualitative research with a descriptive approach. The subjects in this research were 25 class VIII students of SMP Negeri 4 Maniamolo. Data collection was carried out using tests, questionnaires and interviews. The data was analyzed in stages, namely data reduction, data presentation and drawing conclusions. The research results show that the ability to think creatively in solving story problems on SPLDV material is classified as poor, namely the very good category at 8%, the good category at 16%, the fair category at 28%, the poor category at 36% and the poor category at 12%. The research results show that learning independence in solving story problems on SPLDV material is classified as moderate, namely the high category at 8%, the medium category at 56% and the low category at 36%. So it can be concluded that students' creative thinking abilities are more dominant in the sufficient category and students' learning independence is also still dominant in the moderate category. The suggestions put forward in this research are that it is hoped that students will be able to develop their level of thinking to be more active and have more practice solving math problems related to SPLDV material, and teachers should be able to develop students' creative thinking abilities and increase students' learning independence in solving story problems on SPLDV material.